PENGAPLIKASIAN ANALISIS LAYOUT DAN BEP PADA PERUSAHAAN - Harry Indra (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
This research applied two model of analysis, layout and BEP which has its own differentiate but yet still got common things of eficiency for layout or cost.